Environmental Law Innovation For The Digital Age: Menuju Pemeliharaan Lingkungan Yang Lebih Efektif dan Adil - Muhammad Rifki Adnan Ramadhan; Afriansyah Mufthi Akbar; Ivan Nugraha (Lembaga Pengembangan Kinerja Dosen, 2024)
The utilization of technology in environmental law has become crucial in enhancing the efficiency of monitoring and enforcement of environmental violations, with the use of technology-based monitoring systems such as sensors and drones enabling more accurate and real-time monitoring. Engaging inclusive and sustainable community participation is also a key step in achieving environmental justice, with efforts to improve accessibility of environmental information to the public and address challenges such as information gaps and access limitations. Furthermore, addressing the equitable distribution of environmental burdens and benefits among all members of society is a primary focus, by applying the principles of environmental justice and strengthening community involvement in environmental decision-making to reduce social and economic inequalities. Finally, creating an adaptive and responsive environmental legal system is increasingly important as environmental issues continue to evolve in complexity, requiring flexible environmental regulations, monitoring institutions capable of keeping pace with technological and environmental advancements, and collaboration among stakeholders to effectively address future challenges in a comprehensive manner.